2012
DOI: 10.1016/j.jvs.2011.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Primary balloon expandable polytetrafluoroethylene-covered stenting of focal infrarenal aortic occlusive disease

Abstract: The primary use of PTFE-covered stents is a feasible, effective, and safe treatment for focal atherosclerotic lesions in the infrarenal aorta. Comparative studies with traditional treatment modalities, however, are indicated before considering the use of covered stents as standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…This is in keeping with a case series performed by Bruijnen et al, who stented 12 patients with isolated infra-renal aortic disease reporting no cases of restenosis. 11 Our results affirm the conclusion that covered stents are related to an improved outcome in a kissing stent configuration and related to excellent results in isolated aortic lesions. 12 The authors acknowledge that the relatively small number of patients included in the present study accounts largely for the absence of statistically significant univariate predictors of patency.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in keeping with a case series performed by Bruijnen et al, who stented 12 patients with isolated infra-renal aortic disease reporting no cases of restenosis. 11 Our results affirm the conclusion that covered stents are related to an improved outcome in a kissing stent configuration and related to excellent results in isolated aortic lesions. 12 The authors acknowledge that the relatively small number of patients included in the present study accounts largely for the absence of statistically significant univariate predictors of patency.…”
Section: Discussionsupporting
confidence: 86%
“…This is in keeping with a case series performed by Bruijnen et al., who stented 12 patients with isolated infra-renal aortic disease reporting no cases of restenosis. 11 Our results affirm the conclusion that covered stents are related to an improved outcome in a kissing stent configuration and related to excellent results in isolated aortic lesions. 12…”
Section: Discussionsupporting
confidence: 86%
“…Covered stent placement in the aorta has few data on which to base any specific recommendations regarding use. 152 Stents should be sized appropriately to the native aorta, with consideration given for the tissue displaced (especially calcific disease). This may necessitate undersizing the stent relative to the diameter of the native normal-caliber aorta to reduce the risk of rupture, which has been reported with this approach.…”
Section: A Aortoiliac Revascularization: Catheter-based Interventionsmentioning
confidence: 99%
“…Whether stenting increases patency rates over balloon angioplasty alone remains unclear. Rutger et al have shown that the use of PTFE (Polytetrafluoroethylene) -covered stents for isolated atherosclerotic lesions in the infrarenal aorta is safe, feasible, and associated with an excellent outcome [17].…”
Section: Journal Of Vascular and Endovascular Surgery Issn 2573-4482mentioning
confidence: 99%